The association between increasing maternal age at first birth and decreased rates of spontaneous vaginal birth in South Australia from 1991 to 2009. (8th February 2014) - Baghurst, Peter; Robson, Stephen; Antoniou, Georgia; Scheil, Wendy; Bryce, Robert
<x xml:space="preserve">Abstract</x> Background Caesarean section rates in Australia rose over the period 1999–2009, as did maternal age at first birth. The contribution of the rise of maternal age to the rise in caesarean sections remains unclear. Aims To estimate the effect of increasing maternal age on the incidence of emergency caesarean section or instrumental delivery in term singleton first births in South Australia. Methods We undertook a population‐based study of 117 981 term singleton first births, which followed labour during the period 1991–2009, using data from the South Australian Perinatal Statistics Collection. The main outcome measures were deliveries other than spontaneous vaginal births (SVB) (emergency caesarean section or instrumental birth) and emergency caesarean section alone. Logistic regression analysis was performed. Results Increasing maternal age at first birth was found to be associated with delivery other than SVB and emergency caesarean section. The adjusted odds of delivery other than SVB increased multiplicatively by approximately 1.49 (95% CI, 1.47–1.51) per five‐year rise in maternal age, and the odds of emergency caesarean section increased multiplicatively by approximately 1.39 (95% CI, 1.37–1.42) per five‐year rise. Although there are likely to be many reasons for the effect, increases in maternal age at first birth made a contribution in up to 75% of the observed increase in delivery other than SVB from 44.0% to 49.6% over the study period. Conclusions Rising maternal age at first birth appeared to contribute to a large proportion of the increase in deliveries other than SVB in South Australia.